Recovery and detection of methamphetamine-contaminated fingermarks in forensic settings - Sarifudin, Sarah Aliah Amir (2023)
Fingermarks are usually invisible and could be contaminated by exogenous substances such as drugs. Whenever there are drug-related crimes, either clandestine drug manufacturing or distribution and abuse of illicit drugs, fingermark, and the drug substances are the two important pieces of forensic evidence where their evidential values shall be maximised. This study aimed to investigate the detection of methamphetamine-contaminated fingermarks in forensic settings. In this study, fingermarks were developed on eleven types of surface materials using black and white fingerprint powders. The effect of the presence of methamphetamine towards the recovery and interpretation of the fingermark, as well as the immediacy of deposition either as a fingermark deposited on a priorly methamphetamine-contaminated surface or a fingermark deposited on a clean surface but subsequently contaminated by the methamphetamine, were also investigated. The application of fingerprint powder was good in developing fingermarks from any surface; however, its suitability depends on the nature of the surface materials. The choice of fingerprint powders significantly affected the fingermark scoring with F (1, 122.22) = 301.834, p < 0.001. Black fingerprint powder produced better visualisation where the fingermarks on all the eleven surface materials tested in this study were successfully recovered compared to white fingerprint powders; however, fingermarks appeared on quartz countertops and brown melamine particle board surfaces were found more difficult to be recovered. Methamphetamine-contaminated fingermarks could still be recovered using the fingerprint powdering method, but the scoring of fingermarks could be reduced due to an exogenous substance. In determining the immediacy of deposition, methamphetamine crystals at the exterior of the fingermark residue and the distinct separations between the ridge and non-ridge areas of the fingermark could suggest the prior-deposition contaminated fingermark under a scanning electron microscope. Simon’s chemical test, UV-Vis spectrophotometry, and gas chromatography methods were useful in detecting the presence of methamphetamine from the surface-sampled samples. The fingerprint powder particles were less likely to interfere with the positive detection. No association was found between the application of fingerprint powder and the positive detection of methamphetamine by Simon’s test (p = 0.709). To conclude, techniques for detecting illicit methamphetamine-contaminated fingermarks were successfully established.